3-Hydroxysalicylaldehyde 2-furoylhydrazone - Basirun, Wan Jefrey; Ng, S.W.; Ali, H.M.; Puvaneswary, S. (International Union of Crystallography, 2005)
The molecular structure of C12H10N2O 4 was investigated. The molecule was found to be planar and two molecules were stacked over one another at a distance of 3.6 Å. In the compound, the 3-hydroxy substituent was observed to be forming an intermolecular hydrogen bond to the carbonyl O atom of an adjacent molecule. The molecules were linked by hydrogen bonds into a three-dimensional network.